Positive Prevention Reducing HIV Transmission among People Living with HIV/AIDS - Kalichman, Seth C.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2005)
"This book is a 'must read' for those interested in the prevention of HIV transmission. It has enough breadth to provide a general overview of 'prevention with positives' and enough detail to satisfy and educate those already working in this area. Clinicians who want to develop or refine their approaches to counseling patients with HIV will find this book valuable." (Gary Marks, PhD., New England Journal of Medicine, August 4, 2005) The CDC has made a revision in their philosophy underlying recommended prevention techniques to stop the spread of HIV/AIDS. The new approach focuses on "positive prevention", that is, prevention among people living with HIV/AIDS. This important distinction has resulted in the need to reexamine the behaviors around HIV transmission and the approaches to prevention when working within this diverse population. Positive Prevention is a timely volume containing the latest contributions from the top scholars in the field on preventing the spread of HIV/AIDS. Issues covered include unprotected sex with HIV-positive gay and bisexual men; issues around whether disclosure leads to safer sex; mental health and HIV with young adults; the impact of HIV diagnosis on sexual risk behaviors; interventions in community settings; and more. There is also a important chapter on international perspectives on "positive prevention". This volume will serve as an invaluable sourcebook for all professionals working in the field of HIV / AIDS prevention.
An Overview of Prevention with People Living with HIV -- HIV Diagnosis and Risk Behavior -- HIV Disclosure and Safer Sex -- HIV-Positive Gay and Bisexual Men -- HIV-Positive and HCV-Positive Drug Users -- Young People Living with HIV -- Interventions in Community Settings -- Interventions in Clinical Settings -- International Perspectives.
Keywords: Public health; Infectious diseases; Epidemiology; Health promotion; Public Health; Infectious Diseases; Epidemiology; Health Promotion and Disease Prevention